Evaluation of the association between admission systolic blood pressure and the choice of initial antiplatelet therapy for minor ischemic stroke in real‐world - Tingting Liu; Yongle Wang; Xiaoyuan Niu; Yanan Li; Kaili Zhang; Haimei Fan; Jing Ren; Juan Li; Liansheng Ma; Xinyi Li; Xuemei Wu (The Journal of Clinical Hypertension, 2022)
Abstract To evaluate whether admission systolic blood pressure (SBP) is associated with the choice of initial antiplatelet therapy for minor stroke. Eligible patients retrospectively gathered from 2010 to 2018. Finally, 1312 of 1494 patients were divided into three groups: aspirin monotherapy (AM, n = 538, 41.0%), dual antiplatelet therapy with aspirin and load‐clopidogrel (clopidogrel loading dose of 300 mg on the first day, DAPT‐ALC, n = 474, 35.6%), and dual antiplatelet therapy with aspirin and unload‐clopidogrel (clopidogrel 75 mg daily with no loading dose, DAPT‐AUC, n = 300, 22.9%). The mean ± SD age of final patients was 62.0 ± 12.7 years old; 903 (70.9%) participants were male. Patients in the DAPT‐ALC group were more likely to be younger, to arrive earlier, and to have a lower proportion of intracerebral hemorrhage than those in the AM group. DAPT‐AUC group patients were more like to have a history of acute myocardial infarction and less likely to have a history of ICH than the AM group (4.7% vs. 1.7% and .3% vs. 2.6%, p < .05). Overall, there was a likely “S‐shaped” association between the selection of the DAPT‐ALC or DAPT‐AUC scheme and admission systolic blood pressure (P for nonlinearity = .012). Compared with the SBP < 140 mmHg group, the SBP ≥ 180 mmHg group was more likely to be given DAPT‐AUC (OR = 2.92 [1.62–5.26], p < .001) than DAPT‐ALC. Our findings support that admission SBP is associated with the choice of initial antiplatelet, especially when the SBP was greater than or equal to 180 mmHg.